Pipe type and seismic performance in Christchurch, New Zealand - Toprak, S.; Nacaroglu, Engin; Ceylan, Muhammet; Dundar, G.; Cirmiktili, O. Y. (Institute of Physics Publishing helen.craven@iop.org, 2020)
The pipeline damages observed in Christchurch, New Zealand during the 2010-2011 earthquakes provided new insights regarding the seismic performance of pipelines. The water pipeline damages were extensive and water service was interrupted for a long period of time. Meanwhile, unprecedented efforts have been underway following the period right after the first earthquake up to now to obtain and store data related to entire damaged structures, geology, soil conditions, seismicity etc. in the area for the recovery and future planning purposes. These data have been very crucial to study, understand and apply the lessons learnt from these earthquakes and get ready for future earthquakes. This paper focuses on seismic performance of pipelines regarding the pipe type during the MW 6.2 22 February 2011 Christchurch earthquake. Majority of pipeline damages occurred in soil liquefaction areas where differential settlements and lateral strains affected the pipelines adversely. In addition, liquefaction severity parameters such as liquefaction potential index (LPI) and liquefaction severity number (LSN) have been considered in the evaluations of damages. Pipelines in Christchurch consisted of different pipe materials and their performance during the earthquake differed significantly. Geographical information systems (GIS), clustering analyses (fuzzy and k-means methods) and reliability aspects were used in their assessment. © 2020 Elsevier B.V., All rights reserved.
5th International Conference on New Advances in Civil Engineering, ICNACE 2019 -- Kyrenia -- 160101